FEM analysis of a new three-way drainage and pressure reduction system for road tunnels - Zhaolei Teng; Yuanming Liu; Shilong Mei; Yuhang Zhou; Guohua He; Yingxiao Li; Bitao Du (Scientific Reports, 2023)
Abstract For water-rich areas, tunnel elevation arches under high water pressure often cause elevation arch cracking and leakage, bulging and other failures. When the drainage system is not designed properly, these failures occur more frequently, and conventional road tunnel drainage cannot effectively reduce the water pressure at the elevation arch. Therefore, this paper proposes a new concept of "three-way drainage". The three-way drainage system is based on a conventional drainage system with a new drainage inlet at the elevation arch. On this basis, a series of numerical simulation studies are conducted to verify the pressure-reducing performance of the three-way drainage system on the lining. After demonstration and analysis, the three-way drainage concept can not only effectively reduce the water pressure at the elevation arch of the tunnel but also have a significant effect on the overall drainage effect of the tunnel. The factors affecting the performance of the three-way drainage system are assessed by varying the model parameters. It is found that the hydraulic conduction coefficient of the surrounding rock and initial support, the number of reverse diversion holes in the elevation arch, the change in head height, and the change in secondary lining parameters all have a significant effect on the water pressure outside the tunnel.